2014
DOI: 10.1186/1471-2164-15-345
|View full text |Cite
|
Sign up to set email alerts
|

The Netrin-1 receptor DCC is a regulator of maladaptive responses to chronic morphine administration

Abstract: BackgroundOpioids are the cornerstone of treatment for moderate to severe pain, but chronic use leads to maladaptations that include: tolerance, dependence and opioid-induced hyperalgesia (OIH). These responses limit the utility of opioids, as well as our ability to control chronic pain. Despite decades of research, we have no therapies or proven strategies to overcome this problem. However, murine haplotype based computational genetic mapping and a SNP data base generated from analysis of whole-genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…To link our findings further to existing animal literature, we performed computational haplotype-based genetic mapping analyses 48 50 of data from 23 inbred mouse strains for a robust measure of opioid physical dependence, 48 counts of jumps made by morphine dependent mice after naloxone administration. Correlations were calculated for the distribution of the mean number of jumps per strain with known haplotype blocks across strains for CNIH3 and genes encoding AMPAR subunits and proteins involved in alterations of AMPAR subunit composition in response to opioids.…”
Section: Resultsmentioning
confidence: 99%
“…To link our findings further to existing animal literature, we performed computational haplotype-based genetic mapping analyses 48 50 of data from 23 inbred mouse strains for a robust measure of opioid physical dependence, 48 counts of jumps made by morphine dependent mice after naloxone administration. Correlations were calculated for the distribution of the mean number of jumps per strain with known haplotype blocks across strains for CNIH3 and genes encoding AMPAR subunits and proteins involved in alterations of AMPAR subunit composition in response to opioids.…”
Section: Resultsmentioning
confidence: 99%
“…The analgesic effect of opioids might explain the positive association between chronic pain and opioid cessation. In addition, the Netrin-1 receptor gene, DCC, was related to chronic opioid exposure and chronic back pain in both mice and human studies [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…1 Opioid-induced changes in nociceptive thresholds for 23 strains of mice. These data were reproduced from our earlier report [ 18 ]. In panel ( a ) the reduction in mechanical nociceptive thresholds are displayed as a fraction of the baseline thresholds.…”
Section: Resultsmentioning
confidence: 81%
“…Haplotype-based computational genetic mapping (HBCGM) has recently advanced to the point that whole-genome sequence data can be used to identify genetic factors affecting drug responses [ 17 ]. Using this approach, we recently found that the Dcc gene affects OIH and tolerance [ 18 ]. However, highly polymorphic genes have a relatively high probability for matching unrelated phenotypes by HBCGM due to the large number of haplotype blocks that can be formed within the gene.…”
Section: Introductionmentioning
confidence: 99%